The role of colonial missionary chronicles in the Colombian Llanos Orientales region’s configuration and in the social production of differences - Lina Marcela González Gómez (Historia y Sociedad, 2015)
There is significant bibliography on catholic missions one of the most important strategies for the practice of colonial control in America which, for the Colombian case, has particularly focused on showing their economic structure, their evangelistic tasks, and their role in the definition of colonial geopolitics. This article is aimed to give a different perspective about this issue by focusing on the analysis of the chronicles recording the missions elapse. This is performed under the hypothesis that the bases that help understand the configuration of the Llanos Orientales(eastern plains) regional profile as well as the social production of differences can be found in those stories